Cetobacterium alleviates the lipid accumulation in Nile tilapia (Oreochromis niloticus) induced by leucine addition - Wang, Miao; Tang, Chenglin; Liu, Zhigang; Cao, Jianmeng; Wang, Zhang; Lu, Maixin; Yi, Mengmeng; Ke, Xiaoli (Frontiers in Microbiology, 2026)
Deviation from the optimal dietary leucine range has been shown to have negative effects on fish growth and metabolism. This study investigated the dose-dependent effects of dietary leucine on lipid metabolism in Nile tilapia (Oreochromis niloticus). Four diets were formulated: a control diet containing the basal leucine level (2.3% of diet) and three test diets supplemented with 0.8, 1.6%, or 2.4% leucine, respectively. After 12 weeks of feeding, fish receiving ≥ 0.8% supplemental leucine showed significant growth inhibition (lower body weight and total length) and metabolic disorders, including hyperinsulinaemia and elevated serum total cholesterol (TC) and triglycerides (TG) levels, together with increased hepatic lipid-droplet area. Tilapia in the 2.4% leucine-addition group exhibited a markedly higher hepatosomatic index (HSI), whereas blood glucose was significantly reduced in tilapia of the 1.6 and 2.4% leucine-addition groups. Liver transcriptome comparison (2.4% leucine-addition vs. control) revealed activation of amino acid synthesis and the mTOR signaling pathway. qRT-PCR confirmed that excessive leucine up-regulated the expression of key lipogenic genes, such as IRS1 and ACC. 16S rRNA sequencing further revealed a 2.3-fold increase in the relative abundance of Cetobacterium in the intestine of the 2.4% leucine-addition group. Subsequent intervention with Cetobacterium somerae NK01 significantly reversed leucine-induced metabolic disorders, with a decrease in serum TC and TG levels by 7.8 and 10%, respectively, and a 58.3% reduction in hepatic lipid-droplet area. These beneficial effects were associated with the modulation of lipid-related genes, including IRS1, PI3K, SREBP1c, ACC, and FAS. Collectively, the data demonstrated a dual role of leucine in tilapia lipid metabolism: it promoted lipid lipogenesis by activating the mTOR-SREBP1c signaling axis while simultaneously enriching the intestinal symbiont Cetobacterium to alleviate metabolic stress.